Public and patient involvement (PPI) in the design, execution and dissemination of a trial: the BISTRO trial - David Coyle; Paula Ormandy; Nancy Fernandes da Silva; Simon Davies (Health Technology Assessment, 2025)
Background For people receiving haemodialysis, a balance has to be struck between removing sufficient but not too much fluid during a treatment session and maintaining any remaining kidney function they might have. In the BISTRO trial, this study sought to establish if getting the balance right might be improved by the additional use of bioimpedance, a device that measures body fluid composition to help decide how much fluid to remove during dialysis. Designing and executing this trial, which incorporated complex and repeated trial procedures that would be dependent on participant engagement, presented challenges that demanded effective public and patient involvement. Objectives This study aimed to develop an effective public and patient involvement participation model, ensuring that the patient voice was heard by the Trial Management Group, with a Patient Advisory Group undertaking coproduction of all participant-facing documents and communications, including dissemination of the trial results, with the main purpose of maximising participant engagement in the study. Design An open-label randomised controlled trial in which 439 participants from 34 centres were allocated for regular assessments of their bodily fluid content with or without the use of bioimpedance measurements. Interventions Development of an effective public and patient involvement working model that was represented within the Trial Management Group, contributing to protocol design, selection of bioimpedance device, and coproduction of all participant-facing communications including dissemination of trial findings. Main outcome measures Public and patient involvement contribution prior to trial initiation, description of the participant-facing communications, adherence to trial materials, dropout and dissemination of trial findings. Post-trial evaluation by research teams, Patient Advisory Group and co-applicants. Results An effective working model was developed which relied on remuneration of the public and patient involvement patient lead and use of social media (e.g. WhatsApp) to maximise inclusivity. The Patient Advisory Group coproduced with the Trial Management Group a series of communication postcards and newsletters and a web page to support the participants and disseminate the trial results that were highly rated by research teams, but not always passed on to trial participants. Participant adherence to the main trial outcomes was excellent (113.6% urine collections obtained). Potentially avoidable dropout was 14.4%, with 3.6% being clearly attributable to inability or unwillingness to comply with the trial procedures. Reflections by the Patient Advisory Group indicated that they felt valued, involved and listened to but anticipated more direct involvement with the trial participants, recommending that barriers to this be addressed during the trial design and set-up. Limitations Evaluation of public and patient involvement was retrospective and there was a lack of real-time assessment of the impact of public and patient involvement that might have supported a causative link between public and patient involvement interventions and the successful delivery of the trial. Conclusions Public and patient involvement played an important role in the design, delivery and dissemination of the BISTRO trial. Key to this success was the close relationship between the Patient Advisory Group and the Trial Management Group. Given the complexity of the intervention, dropout was reasonably low and did not compromise trial findings, but reasons were not always clear. Prospective gathering of data to capture the impact of public and patient involvement is recommended and direct support for participants facilitated. Funding This article presents independent research funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme as award number 14/216/01. Plain language summary The BISTRO trial was commissioned by the National Institute for Health and Care Research Health Technology Assessment after wide public consultation to establish whether the use of bioimpedance to guide fluid management in haemodialysis patients could slow down the loss of their remaining kidney function. It was clear that the design and conduct of the trial would present particular challenges as it asked a lot of participants over a 2-year period. They would need to collect their urine regularly, engage in the assessment of their fluid status and complete forms that measured aspects of their health. To support patient recruitment and participation in the research, a Patient Advisory Group was set up by the Trial Management Group led by a co-applicant with lived experience of dialysis who in the pre-funding design stage led the kidney failure patient network, hosted by the National Institute for Health and Care Research Devices for Dignity Medtech Co-operative. Prior to commencement of the trial, the network informed its design and the selection of the bioimpedance device, and during the conduct of the trial, the Patient Advisory Group coproduced materials to support both research teams and participants. The trial was successfully completed and gave a clear answer despite interruption by the COVID pandemic. Adherence to urine collections was excellent, despite prior concerns this would prove problematic, and dropout was acceptable. Completion of health questionnaires was comparable to other published studies, but the proportion filled out dropped the longer participants were in the study. Although feedback on trial support and materials was excellent, it remains uncertain to what extent the close collaborative working of the Patient Advisory Group and Trial Management Group was a contributor to the delivery of the trial. It is recommended that this information is collected prospectively during the conduct of trials, provided that it does not add significantly to the burden of investigators or participants.